Samuel Vaughan diary - Vaughan, Samuel
Diary (1787 June 18-September 4) kept by Vaughan on a trip through Virginia, Maryland, and Pennsylvania to Fort Pitt. The volume (44 pages) also includes maps, later notes on the diary entries, and list compiled by his son, Benjamin Vaughan, giving information on Samuel Vaughan's children.
Microfilm edition available
Positive photocopy produced from original in possession of Bertha H. Vaughan.
Merchant of London, England.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Vaughan, Benjamin, -- 1751-1835.; Vaughan family; Fortification -- Pennsylvania; Fort Pitt (Pa.); Maryland -- Description and travel; Maryland -- Maps; Pennsylvania -- Description and travel; Pennsylvania -- Maps; Virginia -- Description and travel; Virginia -- Maps; Merchants